The Development of Online Blended Learning in the Carreer and Technology strand on Developing Electronic Book - สะกะมณี วาทินี; ละลอกน้ำ นคร; พานิชย์ วีระพันธ์ (Journal of Educational Review Faculty of Education in MCU, 2019)
The objectives of this research were to 1) The Development of online Learning Lesson of Blended Learning in the Career and Technology Learning Substance Group on creating of electronic book Of Prathomsuksa 6 Students to meet the efficiency of E1/E2 = 85/85 2) to determine the effectiveness index of online Learning Lesson of Blended Learning in the Career and Technology Learning Substance Group on creating of electronic book Of Prathomsuksa 6 Students 3) To survey the leaners’ satisfaction towards the online tutorials. The population in this study was 60 students in 2 classroom.They were studying in Prathomsuksa 6 at Wattapotharam School, Chonburi province. The samples used in this study were 30 Prathomsuksa 6 students at Wattapotharam School, Chonburi province for the First semester 2018 employed Cluster Sampling technique.They were randomly selected to be 1 classroom with 30 students. It was found that the online Learning Lesson of Blended Learning in the Career and Technology Learning Substance Group on creating of electronic book Of Prathomsuksa 6 Students possessed the efficiency of 86.22/86.44. The effectiveness index Lesson of Blended Learning 0.72. The satisfaction of the students towards online Learning Lesson of Blended Learning in the Career and Technology Learning Substance Group on creating of electronic book Of Prathomsuksa 6 Students with the mean of 4.58 and the standard deviation of 0.54.